Do Delivery Mode and Anesthesia Management Alter Redox Setting in Neonates? - Rakić, Goran; Dobrijević, Dejan; Uram-Benka, Anna; Antić, Jelena; Uram-Dubovski, Jasminka; Andrijević, Ljiljana; Drašković, Biljana (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Objective Fetal-to-neonatal transition is accompanied by oxidative stress. The degree of oxidative damage may depend on several factors, such as delivery type and obstetric anesthesia type. The objective of the study was to determine if the delivery type and obstetric anesthesia type have an impact on oxidative stress levels in newborns.Material and methods A prospective study included 150 newborns divided into three groups: neonates delivered vaginally, via cesarean section in general anesthesia, and via cesarean section in spinal anesthesia. Levels of pH, PaO2, lactate, glutathione peroxidase, and thiobarbituric acid reactive substance were quantified and compared between groups.Results Vaginal delivery was followed by the highest lactate and thiobarbituric acid reactive substance levels and lowest pH, PaO2, and glutathione peroxidase levels. Higher values of thiobarbituric acid reactive substance, PaO2, and glutathione peroxidase and lower pH values were noted in neonates delivered in general anesthesia in comparison to neonates delivered in spinal anesthesia.Conclusions Neonates delivered in general anesthesia were most prone to oxidative stress, while neonates delivered in spinal anesthesia were least affected by reactive oxygen species.
Keywords: oxidative stress; thiobarbituric acid reactive substances; glutathione peroxidase; newborn; pregnancy; anesthesia